EXERCISE-INDUCED BRONCHOSPASM IN CHILDREN - NOT ALWAYS ASTHMA - Ileana Katerina Ioniuc; Monica Mihaela Alexoae; Iuliana Magdalena Starcea; Adriana Mocanu; Elena Hanganu; Luiza Pohaci Antonesei; Catalin Pohaci; Irina Tarnita; Stefana Nangiu; Tatiana Chisnoiu; Ionela Daniela Morariu; Alice Nicoleta Azoicai (Romanian Society of Oral Rehabilitation, 2023)
Exercise-induced bronchoconstriction (EIB) is a dysfunction of the respiratory tract consisting of transient airflow obstruction that occurs during or immediately after physical exercise, being the preferred term to define what was known for years as exercise-induced asthma. Symptoms develop when airways narrow as a result of physical activity. As many as 90 percent of people with asthma also have EIB, but not everyone with EIB has asthma. EIB is defined as the coexistence of at least two of the following symptoms: dyspnea, cough, wheezing, shortness of breath and chest pain, combined with the decrease of forced expiratory volume in one second (FEV1). Perception of these symptoms may restrain children's ability and willingness to exercise. The pathophysiology of the process and the severity of bronchospasm depend on the level of ventilation, temperature and humidity of the inspired air. The mechanism is related to thermal hyperemia and congestion of small vessels in the bronchial wall. Most of the symptoms are non-specific, the differential diagnosis including chronic lung diseases and certain cardiovascular diseases or gastroesophageal reflux. For the diagnosis of this entity, a series of challenge tests can be used: at graded exercise, voluntary hyperpnea, methacholine, mannitol, hypertonic saline or histamine, FEV1 decreasing by 10-20% depending on the chosen test. Effective treatment includes preventive therapy - prior administration of a beta 2 agonist and/or antileukotriens, or regular CSI treatment in children with asthma that reduce the number of mast cells required for this type of response.